Reproductive behavior of Eidmanacris corumbatai garcia (Orthoptera: Phalangopsidae) - Prado, Rogilene [UNESP] (Springer Nature, 2006)
Adult males of Eidmanacris corumbatai Garcia have reduced tegmina without stridulatory apparatus. For this reason, they developed other means of intra-specific communication. During courtship, the males use a combination of foreleg drumming and waving of the antennae, in addition to chemical signaling through pheromones. The females become receptive to copulation when the males expose their metanotal gland. This gland, located on the male metanotum, is also a source of substances on which females feed before receiving the spermatophore. During copulation, the female destroys the apex of the metanotal gland to gain access to the secretion released by this structure.
Keywords: Cricket; Metanotal gland; Nuptial gift; animal; cannibalism; copulation; exocrine gland; female; grasshopper; male; reproduction; ultrastructure; Animals; Cannibalism; Copulation; Exocrine Glands; Female; Grasshoppers; Male; Reproduction; Orthoptera; Phalangopsinae